ТЕКТОНИКА И ПЕРСПЕКТИВЫ НЕФТЕГАЗОНОСНОЕ ДОМАЙКОПСКИХ ОТЛОЖЕНИЙ РОССИЙСКОЙ ЧАСТИ ЧЕРНОГО МОРЯ - Головинский В.И.; Кузнецова Н.Ф. (My University, 2003)
Статья составлена по данным морских геофизических исследований. Рассмотрены формирование и строение верхнемезозойских и нижнекайнозойских осадочных отложений северо-восточной части Черного моря. Сделаны выводы о перспективах нефтегазоносности этих отложений. Как высокоперспективные оцениваются предполагаемые рифовые ловушки верхней юры и мела.

The article is composed on the basis of offshore geophysical investigations. Evolution and structure of Upper Mesozoic and Lower Cenozoic sedimentary deposits of North-East Black Sea is looked through. The conclusion about their oil and gas potential is made. Conjectural reef-traps in Jurassic and Cretaceous deposits could be considered as high perspective.
Keywords: Cenozoic; Cretaceous; Jurassic; 551.242.2:553.98(477.75); Cenozoic; Кайнозой; Mesozoic::Cretaceous; Мезозой::Меловая; Мезозой::Юрская; Mesozoic::Jurassic